I'll be your mirror art and the digital screen - Hearst, Alison; Kholeif, Omar; Ryan, Tina Rivers; Suler, John R. 1955- (Modern Art Museum of Fort Worth, 2023)
Surveying some 50 years of groundbreaking art related to digital technology and the screen, I'll Be Your Mirror examines how technologies such as home computers, smartphones and TV have affected art and life over the past five decades. It traces a trajectory stretching back to the late 1960s, a watershed moment in the rise of the screen in the home. Today, accelerated by the pandemic, our daily life is mediated through screens for work, entertainment and sociality
Aus dem Impressum: "This catalogue is published on the occasion of the exhibition 'I'll Be Your Mirror: Art and the Digital Screen', curated by Alison Hearst and organized by the Modern Art Museum of Fort Worth, on view February 12 to April 30, 2023."
Keywords: Geschichte; Computerkunst; Videokunst; 1900-2099; Art and technology / Exhibitions; Digital media / Exhibitions; Computer art / Exhibitions; Video art / Exhibitions; Art, Modern / 20th century / Exhibitions; Art, Modern / 21st century / Exhibitions; Art and technology / (OCoLC)fst00815441; Art, Modern / (OCoLC)fst00816615; Computer art / (OCoLC)fst00872033; Digital media / (OCoLC)fst00893716; Video art / (OCoLC)fst01166389; Exhibition catalogs / (OCoLC)fst01424028; Ausstellungskatalog -- Modern Art Museum of Fort Worth -- 12.02.2023-30.04.2023 -- Fort Worth, Tex.; Bildband